(untitled) (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
Global shocks such as pandemics, economic crises and environmental disasters are irreversibly changing life and business, and require solidarity and coordinated action at the international level. The transition to a circular economy, based on rational use of resources, reducing emissions of gases and waste, preserving the environment, is a central part of the European Green Agreement and the NGEU recovery plan from the COVID-19 pandemic. In this regard, the subject of research in this paper are the concept of circular economy, CE business models and ways to reduce the effects of the COVID-19 crisis on human lives and the RS economy, and create conditions for recovery of the national economy. Derived from a subject, the aim of the paper is to provide an overview of the current macroeconomic variables RS and EU, analyze the recovery measures proposed by our country and those suggested by the EU in the Green Agenda for the Western Balkans. The expected result is the identification of specific regulatory, institutional and economic actions of the transition to a circular economy that should be undertaken on the path to healing the RS economy, and implemented at companies with the greatest potential for transition to CE business models.